A Government Tax Subsidy. - Askari, Hossein; Cain, Patricia; Shaw, Richard (The Accounting Review, 1976)
Many tax advisors indicate that tax-exempt bonds, such as municipals, are very attractive for people in high tax brackets; for such people, the tax exemption of interest payments can be significant. The U.S. Congress, being aware of the obvious tax loophole, has legislated against such an advantageous combination. The general rule, then, is that a tax-payer's interest payments will not be tax-deductible if the debt has been incurred to finance the purchase of tax-exempt bonds. However, there are several important exceptions to this rule. The most obvious, is the fact that the rule does not apply to interest on securities which are partially tax-exempt. An individual taxpayer simultaneously could hold tax-exempt bonds, while at the same time deducting interest charges from gross income to reach his or her taxable income. The results of this study indicate three major points. First, given, the present tax treatment of municipals, many taxpayers can profit by borrowing at available rates and investing in lower yielding municipals. Second, the profitable tax bracket has been lowered as the general level of interest rates has risen. Finally, given that the U.S. tax structure is based on nominal rather than real income, inflation increases an individual's marginal tax bracket; thus, more people will find the acquisition of municipals profitable.